A Project Management Office Transformation Roadmap Based on the Project Management Office Value Ring in an Indonesian Insurance Firm - Zubaidah, Takayani Febrianti; Raharjo, Teguh; Sucahyo, Yudho Giri (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
The transformation of the Project Management Office (PMO) has become an important factor in improving organizational performance and value generation inside financial institutions. This study investigates the progress of the PMO in one of the biggest insurance companies in Indonesia, utilizing the PMO Value Ring 26 Functions framework as the primary analytical tool. Established in 2022, the PMO is a developing governance unit that aims to shift from procedural compliance to strategic value generation. This exploratory qualitative case study employs semi-structured interviews, document analysis, and a systematic literature review to assess the PMO’s current maturity level, identify transformation challenges, and propose a three-year strategic development plan. According to the findings, the PMO at the insurance company now serves as a governance facilitator, with limited capabilities in value measurement, stakeholder engagement, and benefit realization. Using the PMO Value Ring 26 Functions model, the study recommends a structured transformation path that prioritizes governance integration, capability enhancement, and performance-based value delivery. The findings benefit both academic and practical sectors by contextualizing the PMO Value Ring framework within a developing economy and providing actionable insights for firms looking to create value-driven PMO maturity in regulated industries.